2019
DOI: 10.1007/s10865-019-00084-7
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the interconnectedness of fatigue, depression, anxiety and potential risk and protective factors in cancer patients: a network approach

Abstract: Receiving a cancer diagnosis has a major impact on patients' lives. One of the most prevalent long-term sideeffects of cancer and its treatment is fatigue. Patients who suffer from severe fatigue also often suffer from symptoms of depression and/or anxiety (Donovan et al., 2013; Hofman et al., 2007; Zhu et al., 2017). In addition, depression and anxiety often co-occur in cancer patients (Mitchell et al., 2011). Multiple studies have demonstrated high correlations among these three problem areas in cancer patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
74
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(81 citation statements)
references
References 57 publications
7
74
0
Order By: Relevance
“…nodes) indicate conditional dependence relations. Accordingly, if an edge exists between two nodes, this means these nodes are associated after controlling for all other nodes in the network (Schellekens et al 2020). Finally, the algorithm used to plot the networks aims to place highly correlated nodes closer together, and nodes with fewer or weaker correlations are placed in peripherals of the graph (Fruchterman and Reingold 1991).…”
Section: Network Estimationmentioning
confidence: 99%
See 2 more Smart Citations
“…nodes) indicate conditional dependence relations. Accordingly, if an edge exists between two nodes, this means these nodes are associated after controlling for all other nodes in the network (Schellekens et al 2020). Finally, the algorithm used to plot the networks aims to place highly correlated nodes closer together, and nodes with fewer or weaker correlations are placed in peripherals of the graph (Fruchterman and Reingold 1991).…”
Section: Network Estimationmentioning
confidence: 99%
“…Cramer et al (2010) suggested that "etiological factors" such as stressful life events can provide insight into the complex mechanisms underlying bridge symptoms between anxiety and depression. However, only a few studies included risk factors in network models to date (Pereira-Morales et al 2019;Schellekens et al 2020). For example, Schellekens et al (2020) investigated how risk and protective factors were interconnected with symptoms of depression, a fatigue sum score and one anxiety symptom ("I felt fearful") in cancer patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even when patients are screened "positive," the complete picture of difficulties and impairments that are likely to ac-company moderate to severe depressive symptoms is not clear. Research with other cancer types would suggest that there are cooccurring stressors and cognitive and behavioral disruptors, and they too may impede cancer patients' coping with the diagnosis and decision-making as do depressive symptoms [29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Having identified these patients, the preeminent aim was to detail and discuss the co-occurring negative emotions (stress), impairments (quality of life, functional status, symptoms), and negative perceptions of one's life and illness that co-occurred. To do this was significant because the latter factors foster the maintenance of depressive symptoms and, conversely, depressive symptoms increase the frequency/severity of these sources of impairment and disability [31,32,[34][35][36][37][38]. Moving beyond PHQ-9 classification, the goal was provision of clinical descriptions for providers and researchers alike of the common psychological, behavioral, and symptom comorbidities experienced by such individuals, ones that, along with depressive symptoms, may impair patients' coping and functioning when they are to make choices and begin lung cancer treatment [39].…”
Section: Introductionmentioning
confidence: 99%